Evaluation Of Cash Withdrawal Procedures Based On PP No. 12 In North Sulawesi - MAMAGHE, Olivia Cristina; MORASA, Jenny; WALANDOUW, Stanley Kho (PT Keberlanjutan Strategis Indonesia, 2023)
Cash Disbursement Accounting Systems and Procedures will help expedite the management of company activities if all its components run according to proper procedures. The aim of the study is to find out that the accounting system for cash disbursements at the National Unity and Regional Politics Agency of North Sulawesi Province has been in accordance with PP No. 12 of 2019. The method used in this study is descriptive qualitative data, namely data presented in the form of a clear and detailed explanation in nature with data collection methods through interviews, observation, documentation. The results of the study show that the Regional Political and National Unity Agency of North Sulawesi Province in the Cash Disbursement Accounting System and procedure managed by the Accounting Section uses the Local Government Information System Application (SIPD) and the Financial Management Information System (FMIS) Application. In implementing this application there are obstacles experienced, while these obstacles are the internet network which is still not good and errors often occur due to viruses in the application which result in problems in inputting application data resulting in delays in issuing Payment Request Letters (SPP) which slows down the disbursement process funds, as well as a lack of human resources (HR) in using this application.